2020
DOI: 10.2147/idr.s236200
|View full text |Cite
|
Sign up to set email alerts
|

<p>Whole-Genome Analysis of Two Copies of <em>bla</em><sub>NDM-1</sub> Gene Carrying <em>Acinetobacter johnsonii</em> Strain Acsw19 Isolated from Sichuan, China</p>

Abstract: Purpose: To characterize the genetic feature of the carbapenems resistant Acinetobacter johnsonii strain Acsw19 isolated from municipal sludge. This strain was found to carry two copies of bla NDM-1, cmlB1-like gene, and bla OXA-211-like gene along with other 8 antimicrobial resistance genes, 3 plasmids, 15 genomic islands and 8 prophages. Methods: A carbapenem-resistant Acinetobacter johnsonii strain Acsw19 isolated from municipal sludge was subjected to whole-genome sequencing (WGS) via the PacBio and Illumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
2
1
Order By: Relevance
“…Our study also identified the existence of tandem copies of the bla NDM-1 gene in the pST_HI2_NDM-1. To our knowledge, the structure of the IS CR1 unit (IS CR1 - dsbD - trpF - ble - bla NDM-1 -IS Aba125 Δ1) with the tandem copies in this study is different from that previously reported [ 38 , 39 ]. Two tandem copies of the IS CR1 unit ( sul1 - arr - 3 - cat - bla NDM-1 - ble -IS CR1 ) were reported in the E. coli Y5 chromosome (CP013483) in 2016 [ 18 ].…”
Section: Discussioncontrasting
confidence: 85%
“…Our study also identified the existence of tandem copies of the bla NDM-1 gene in the pST_HI2_NDM-1. To our knowledge, the structure of the IS CR1 unit (IS CR1 - dsbD - trpF - ble - bla NDM-1 -IS Aba125 Δ1) with the tandem copies in this study is different from that previously reported [ 38 , 39 ]. Two tandem copies of the IS CR1 unit ( sul1 - arr - 3 - cat - bla NDM-1 - ble -IS CR1 ) were reported in the E. coli Y5 chromosome (CP013483) in 2016 [ 18 ].…”
Section: Discussioncontrasting
confidence: 85%
“…In addition to some clinical isolates, two sewage strains (Acsw19 and WCHAJo010049) and a strain collected from pig feces (18QD2AZ57W) had the largest amount of ARGs. In this regard, Tang et al determined that strain Acsw19 has 12 ARGs in plasmids and in the chromosome (10). Considering the OXA ␤-lactamases, we found several families: OXA-211-like, OXA-58-like, and OXA-23-like.…”
mentioning
confidence: 58%
“…The members of the Acinetobacter genus frequently possess multiple plasmids which are the key players in the adaptability of Acinetobacter spp. to various living conditions in the environment and in the clinical setting (Zong and Zhang 2013 ; Tang et al 2020 ; Maslova et al 2022 ). In our study, plasmid-related contigs represented just a minor fraction of the RB2-047 genome (less than 2.5%) as identified by mlplasmid server v2.1.0.…”
Section: Discussionmentioning
confidence: 99%